STRATEGI MEDIATOR NON HAKIM UNTUK MENCAPAI KEBERHASILAN DALAM MEDIASI PERCERAIAN DI PENGADILAN AGAMA BANGIL - Faizzati, Savvy Dian (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
Divorce mediation in the Bangil Religious Court plays an important role in resolving domestic conflicts peacefully. This study explains the importance of mediation as an alternative to resolving disputes in court and highlights the challenges faced in the mediation process. The writing method used in this article is an in-depth literature review and analysis of mediation practices in the Bangil Religious Court. Data collection was carried out through observation, interviews and documentation related to divorce mediation practices in the Bangil Religious Court. This study covers various strategies applied by non-judge mediators, including religious, psychological, beautiful past, family, and mathematical logical approaches. This study shows that the success of divorce mediation is highly dependent on the mediator's ability to apply appropriate strategies, taking into account the cultural, psychological, and social contexts of the conflicting parties. This study makes an important contribution to the development of mediation practices in the religious court environment, especially in the context of divorce.